Prevalence of School Bullying in Higher Secondary School Students and Myths Related to Bullying Among Students: Understanding the Prevalence and Perspectives of Bullying Among Higher Secondary School Students (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Bullying is one of the burning issues in schools and it is one of the national importance issues in schools for every country around the globe. An abundance of researches points out the huge negative impacts on students who are involved in bullying by one way or another. It require the attention and interventions of adults to address and resolve bullying incidents among students. This study, giving importance and light to the voices of 11th and12th graders in higher secondary school of Kashmir and try to find out the prevalence of bullying. It not only tried to understand the various perspectives of bullying but also tried to understand students perception regarding bullying. The study involves 1103 students which was randomly selected among the three regions of Kashmir where male students was 501 and female students was 502 (n=1103). Mixed methods approach was used in the study in which both survey and focus group discussion methods was integrated. Data from the Turkish Peer Bullying Survey Questionnaire (Pişkin, 2010) provided detailed student-reported data on the nature and extent of bullying. Initial review of the survey results in the form of frequency statistics on each question provided baseline data from which focus group questions emerged.Statistical analysis of the survey data generated the quantitative portion of this study while focus group data generated the qualitative portion of this study. The survey revealed that about 25.8 percent of the students in the sample experienced some sort of bullying in the past month with verbal bullying as the most common type of bullying experienced. Themes that emerged from focus groups revolved around confusion regarding the definition of bullying, confusion about bullying, Physical appearance, Impact of bullying and coping behaviour. Finally, participants discussed specific forms and motives of bullying.